To be seen, heard, and loved the polymediated exchanges of emotional support between Filipino migrant parents and their adult left-behind children - Acido, Mark Christian J.; Bernal, Danica Mai N.; Solis, Randy Jay C. (Quezon City University of the Philippines Diliman, 2025)
This thesis explored how transnational families exchanged emotional support through polymedia. We conducted in-depth interviews with ten dyads of migrant parents and their adult left-behind children and observed their Facebook posts to examine patterns of emotional support exchange. Guided by Madianou and Miller’s (2012) Polymedia Theory and the integrated concepts of the need for affect and transnational affect, we analyzed how communication practices were shaped by both technological affordances and emotional tendencies. Our findings revealed that transnational families often deal with homesickness, worries about other family members, stress from school and work, and household responsibilities. These challenges are communicated to ease emotional burden and selectively disclosed or avoided to protect the other member from additional burden and to maintain an image of independence and strength. To manage this, they move between platforms or switch between features, to afford greater control in their digital presence in ways that align with their own emotional needs and intentions, and those of the other person. The study also unveiled that these emotional support exchanges in polymedia manifested pakikiramdam and pakikiisa as key Filipino cultural values. With this, we concluded that labor migration continued to influence the emotional landscape of transnational families, with both migrant parents and adult left-behind children actively and intuitively co-constructing emotional support through polymedia.
Thesis
Keywords: Children of migrant laborers -- Philippines; Communication in families -- Philippines